Diet transformation in Africa: The case of Ethiopia - Hassen, Ibrahim Worku; Dereje, Mekdim; Minten, Bart; Hirvonen, Kalle (International Association of Agricultural Economists, 2017)
Africa's food systems are changing fast amid rapid economic growth, emerging urbanization, and structural transformation. In this study, we use four rounds of nationally representative data from Ethiopia to document changes in household food consumption patterns over a period of unprecedented economic growth. We find that while the share of food in the total consumption basket is declining, food quantities and calorie intakes have considerably increased between 1996 and 2011. A decomposition analysis suggests that this was mostly driven by improvements in household incomes—a finding that is consistent across the calorie distribution. Also, the content of the food basket is changing with a gradual shift toward high‐value foods such as animal products, fruits and vegetables and processed foods. Overall, this diet transformation has important implications for the food security debate and for agricultural and food policy in the country.